THE ANALYSIS OF POLITENESS STRATEGIES ON EFL STUDENTS’ CHATTING GROUP INTERACTIONS - Yuli Tri Amanda; Rina Herlina; Ratnawati Ratnawati (Universitas Galuh, 2021)
This paper reported the analysis of the practice of politeness strategies used in WhatsApp group chatting interactions among EFL students. Intermediate level of English Education Program in one of private universities in West Java was employed because they are assumed to interact in WhatsApp group chatting. Furthermore, two research questions were formulated such as follows: 1) what kinds of politeness strategies do EFL students apply in WhatsApp chatting group interactions? and 2) what is the most dominant politeness strategy realized in EFL students’ chatting group interactions? This study utilized descriptive qualitative study to analyze and interpret the realization of politeness strategy used by the EFL students in WhatsApp chatting group interactions. The results revealed that the students used four politeness strategy types. They were bald on-record, positive politeness strategy, negative politeness strategy, and bald off-record. Then, the most dominant type of politeness strategy in WhatsApp chatting group interactions was positive politeness strategy (47.1%). Based on the results, it was concluded that the EFL students used the entire types of the politeness strategy in the interactions of group chatting in which positive politeness strategy were used the most frequently by the students. Keywords: Teaching speaking, Team Game Tourna